Effect of options “Americanization” reform on underlying market dynamics: a multifractal analysis - Fan, Limin; Fu, Zhongshuo; Yang, MengFei; Lv, Dayong (Frontiers in Physics, 2025)
IntroductionThis paper investigates the effect of a major institutional reform on the Shanghai Futures Exchange: the change in the exercise style of its gold futures option contracts from European to American (“Americanization” reform). We aims to examine the reform’s impact on the efficiency of the gold futures market (the underlying of gold futures options) and the complexity of the cross correlation between gold futures and spot markets.MethodsThe Multifractal Detrended Moving-Average Cross-Correlation Analysis (MF-X-DMA) method is employed in this study. Additionally, the nonlinear Granger test is used to assess the directional predictive relationship between the gold futures and spot markets.ResultsThe MF-X-DMA results indicate that the “Americanization” reform improves the efficiency of the gold futures market but increases the complexity of the cross correlation between gold futures and spot markets. Moreover, the nonlinear Granger test shows that the unidirectional predictive lead from the futures to the spot market diminishes after the reform.DiscussionOur findings suggest that the price discovery function transitions from a simple leader-follower model to a more sophisticated, synchronized system. This study contributes to related literature by providing empirical evidence on the market effects of different option exercise styles from the multifractal perspective.